Literacy and Power - Janks, Hilary (Language, Culture, and Teaching Series, 2010)
‘This is a map of the field of critical literacy – drawn with precision and care. Our guide on the journey is a scholar and teacher, political activist and woman warrior of the greatest strength and wisdom.’ Alan Luke, Queensland University of Technology, Australia ‘Hilary Janks argues that to critically change the educational system you need to understand the interrelationship between language and power. Her framework of dominance, diversity, access and design constitutes a complete theory of critical literacy, one that explains the successes and failures of past and current educational movements. Her thinking has helped me and the U.S. and Canadian teachers I work with outgrow our very selves as we plan new, more powerful, and more critical ways to change education.’ Jerome C. Harste, Indiana University, Bloomington, USA ‘Unlike the biblical prophets, Janks is honoured in her own country, South Africa, for her enormous contribution to language and literacy education in complex linguistic and socio-cultural contexts. As a writer, her special gift is to make the complex accessible in ways that move readers to cry, to laugh, and most of all, to begin or to renew a commitment to critical literacy teaching and research.’ Yvonne Reed, University of the Witwatersrand, Johannesburg ‘Readers who know Janks’ ground-breaking work with critical language awareness with teachers and learners in South Africa have been waiting for this book. For those who don’t, now at last there’s an opportunity to learn how to make critical discourse analysis a central part of a pedagogical repertoire for critical literacy. Immediately helpful to teachers, teacher educators and researchers who are concerned with literacy and power, this fabulous book provides a review of key theory, original approaches to text analyses, and illuminating accounts from classrooms. It makes you want to teach. This will become the essential guidebook for language and literacy educators and researchers.’ Barbara Comber, University of South Australia ‘Hilary Janks develops an innovative model of critical literacy which makes a major contribution to the field. You will look at texts in new ways after reading this book. It will transform your understanding of how language works, it will give you new insights into language and politics in South Africa, and it will provide a principled basis for rethinking the teaching of language and literacy in your own context.’ Roz Ivaniĉ, Lancaster University, UK ‘Admirers of Janks’ scholarship will welcome Literacy and Power and recognise its qualities of lucidity, argumentative coherence, courage and compassion. With its organisation around four interdependent themes of domination, access, diversity and design, this book is the best introduction to critical literacies around.’ Terry Locke, University of Waikato, New Zealand